2022
DOI: 10.3389/fmicb.2022.1017488
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility to polymyxin B and other comparators against Gram-negative bacteria isolated from bloodstream infections in China: Results from CARVIS-NET program

Abstract: ObjectiveTo investigate the bacterial distribution and antimicrobial resistance profile of clinical isolates from Gram-negative bacteria bloodstream infections (GNBSI) in China.MethodsThe clinical bacterial strains isolated from blood culture were collected during April 2019 to December 2021 in 21 member hospitals of China Bloodstream Gram-negative Pathogens Antimicrobial Resistance and Virulence Surveillance Network (CARVIS-NET). Antibiotic susceptibility test was conducted by broth microdilution method recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
(29 reference statements)
0
6
1
Order By: Relevance
“…Similarly to our study, Wang et al found that the mean AUC ss, 24 h of PMB in their renal insufficiency group was higher than in their normal renal function group, with marginal significance ( Wang et al, 2021a ). Moreover, some clinical studies have demonstrated that the patients with PMB-associated AKI had higher AUC ss, 0–24 h ( Xu et al, 2022 ; Yang et al, 2022 ), higher baseline serum creatinine levels, or lower baseline glomerular filtration rates compared to patients without PMB-associated nephrotoxicity ( John et al, 2017 ; Xi et al, 2022 ; Xu et al, 2022 ). These results support the speculation that patients with renal dysfunction are more likely to develop higher PMB exposure and that the dosing regimen of PMB should be adjusted in patients with renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to our study, Wang et al found that the mean AUC ss, 24 h of PMB in their renal insufficiency group was higher than in their normal renal function group, with marginal significance ( Wang et al, 2021a ). Moreover, some clinical studies have demonstrated that the patients with PMB-associated AKI had higher AUC ss, 0–24 h ( Xu et al, 2022 ; Yang et al, 2022 ), higher baseline serum creatinine levels, or lower baseline glomerular filtration rates compared to patients without PMB-associated nephrotoxicity ( John et al, 2017 ; Xi et al, 2022 ; Xu et al, 2022 ). These results support the speculation that patients with renal dysfunction are more likely to develop higher PMB exposure and that the dosing regimen of PMB should be adjusted in patients with renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of extensively drug-resistant Gram-negative bacteria (XDR-GNB) has become a major global health challenge because of the rapid resistance transmission, increasing treatment difficulties, and association with high morbidity and mortality rates ( Borer et al, 2009 ; Cassini et al, 2019 ). Polymyxins including colistin and polymyxin B (PMB) have excellent antibacterial activity against the majority of XDR-GNB as reported by recent surveillance surveys ( Diekema et al, 2019 ; Xi et al, 2022 ) and have been revived as the last-resort therapeutic opinion for XDR-GNB infections ( Katip et al, 2020 ; Katip et al, 2021 ; Liu et al, 2023 ). PMB is an active drug without requiring conversion to colistin after its administration, whereas colistin must be administered as an inactive prodrug, colistin methanesulfonate, to then be converted to colistin in vivo , which could be slow and incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…The assumed second-line regimen of intravenous polymyxin B combined with high-dose meropenem was applied to both the intervention and comparator groups. c The data were sourced from the study by Peiyao Jia et al [22] d The data were sourced from the study by Jingyuan Xi et al [23] The model took antibiotic resistance into account in assessing outcomes. Table 1 summarizes the baseline pathogen distribution and resistance rates to ceftazidime-avibactam and meropenem among major pathogens causing HAP/VAP.…”
Section: Treatment Comparisonsmentioning
confidence: 99%
“… 1 Another investigation reported a rate of 4.9% for P. aeruginosa among 1939 isolated gram-negative bacteria from 21 hospitals in China between April 2019 and December 2021. 2 Notably, most of the bacteriological susceptibility tests from various tissue samples indicated that the strain was sensitive to polymyxin B, indicating that the minimum inhibitory concentration (MIC) of polymyxin B against this strain was less than 2 mg/L. 2 Polymyxins B was initially employed in the 1940s but was swiftly discontinued due to concerns of neurotoxicity and nephrotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Notably, most of the bacteriological susceptibility tests from various tissue samples indicated that the strain was sensitive to polymyxin B, indicating that the minimum inhibitory concentration (MIC) of polymyxin B against this strain was less than 2 mg/L. 2 Polymyxins B was initially employed in the 1940s but was swiftly discontinued due to concerns of neurotoxicity and nephrotoxicity. However, it has been re-recommended, particularly for carbapenem-resistant gram-negative organisms that retain high antimicrobial susceptibility to polymyxins B, in recent years.…”
Section: Introductionmentioning
confidence: 99%